Evaluation of clientele impact of science exhibits - Talisayon, Vivien M. (1992)
An impact evaluation model across time and clientele groups was used to evaluate exhibits of two Science Centers in Metro Manila. Immediate impact on majority of grade school to high school students, based on questionnaire and interview data, was great interest in science and science career choice. Short-term and long-term impact indicated lower student percentages. Student quiz performance was average. Experts highly rated exhibits' alignment to national goals. Students preferred manipulative exhibits producing sound, light and motion.
Keywords: Science -- Exhibitions